Value-at-Risk Estimation with Normal Distribution Approach on Stock Return of BBNI and BBRI - Susanti, Dwi (Operations Research: International Conference Series, 2022)
This paper discusses risk analysis on a single stock return. Stock data analyzed are shares of BBNI and BBRI. The method used is Value-at-Risk with a normal distribution approach. The steps are, after obtaining stock returns, then the value-at-risk (VaR) is estimated using a normal distribution approach. Then a back-test is carried out to measure the performance of risk measures. The results of the analysis show that VaR for BBNI and BBRI produces a small QPS close to zero. This shows that VaR with the normal distribution approach is more consistent and can be used to measure risk for BBNI and BBRI.Â